BREAKEVEN ANALYSIS WITH CONTRIBUTION MARGIN METHOD AS A PROFIT PLANNING IN CV. SUGENG BARU - Kristanti, Ika Neni (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2015)
Breakeven analysis is one of the most important financial analysis in corporate financial planning. Break-even point is the point at which total cost equals total revenue. Breakeven analysis is used to determine the level of sales and product mix needed just to cover all the costs incurred during that period. And to reach the breakeven point, profit target is zero. Contribution margin is the difference between the sales value of the variable costs. Contribution margin can be used to cover fixed costs, and if still left the rest is profit. If management wants to know the breakeven sales quantity, the total contribution margin must equal the total amount of fixed costs. CV. Sugeng Baru is a manufacturing company engaged in the production and the production of paving and building block. CV. Sugeng Baru manufactures its products in large quantities and also accept orders from customers. Therefore, companies need a breakeven calculation to obtain a clear accounting information in the context of short-term profit planning. The results of the analysis break-even point of sales (in rupiahs) in October 2013 amounted to Rp 10,790,885, in November 2013 amounted to Rp 10,790,885, and in December 2013 amounted to Rp 10,762,032. Break-even point (in units) in October is a 4,796 units for paving and 1,199 units for building blocks, in November is a 4,796 units for paving and 1,199 units for building blocks, in December is a 4,784 units for paving and 1,196 units for building blocks. Profit target in October amounted to Rp 10,150,000 and the units must be sold is a 16,884 units for paving and 4,221 units for building blocks. Profit target in November amounted to Rp 10,130,000 and the units must be sold is a 16,868 units for paving and 4,217 units for building blocks. Profit target in December amounted to Rp 9,740,000 and the units must be sold is a 16,356 units for paving and 4,089 units for building blocks. Keywords: break-even point, fixed costs, variable costs, contribution margin.